Two morphologically distinct groups of the Calypogeia fissa complex were found in Europe - Buczkowska, Katarzyna; Sawicki, Jakub; Szczecińska, Monika; Rosadziński, Stanisław; Rabska, Mariola; Bączkiewicz, Alina (Biodiversity: Research and Conservation, 2012)
Two genetically distinct groups (PS and PB) detected previously within the C. fissa complex in Europe were studied with respect to 47 morphometric characters. The two examined groups differed statistically significantly with respect to 34 morphological traits. The forward stepwise method of discriminant analysis showed that the set of diagnostic characters could be limited to nine. The best diagnostic features were morphological characters describing the shape of leaf: length and width of leaf, height of dorsal part and distance from the apex to the ventral base of the leaf, length of the 3rd coordinate of the leaf, and underleaf width as well as characters of the stem: length of internodes and size of internode cells. Plants of the PS group were smaller (shoot width range from 922-1780 μm) than plants of the PB group (1600-3900 μm). Based on genetically identified samples, classification functions for each group were computed and the derived functions were used for the classification of samples from the herbarium collections. The principal component analysis and dendrogram constructed on the basis of Euclidean distance, using the set of diagnostic characters, divided the examined samples into two groups that correlated with groups detected by isozyme markers. Results of multivariable analysis showed that it is possible to satisfactorily characterise morphologically both genetically distinct groups of the C. fissa complex.